Ketahanan Usaha Kecil, Mikro Dan Menengah (Umkm) Dalam Masa Pandemi Covid 19 Melalui Pemasaran Online Instagram - Putu Ayu Sriasih Wesna (Universitas Warmadewa, 2020)
The general problem that occurs in Sanding Village is based on the results of our visits to the community, especially in the field of micro, small and medium enterprises (MSMEs) that significant problems occur, including the lack of qualified workers to assist in the process of developing products produced by local communities. This happened because of the lack of interest in the community in cultivating home businesses or micro, small and medium enterprises (MSMEs) so that the people in Sanding Village mostly work as construction workers and other jobs, besides that due to the COVID-19 pandemic it is also an obstacle, because it automatically causes income. The community in this business has decreased due to reduced orders for their products, in addition to that another problem presented by business actors is the lack of reach in marketing their products due to a lack of knowledge about the use of gadgets and the internet, especially social media.